The Effect of Wordwall-Assisted Discovery Learning on Grade XI Students’ Critical Thinking Skills - Elna Lisnawati; Sri Nopita Primawati (Lombok Institute, 2026)
This study aimed to determine the effect of Wordwall-assisted discovery learning on the critical-thinking skills of Grade XI students at SMAN 01 Montong Gading in the topic of the human reproductive system. A quantitative quasi-experimental approach with a pretest–posttest control-group design was employed. The sample comprised two classes selected through purposive sampling: Class XI-F.1 as the experimental group and Class XI-F.2 as the control group. The instruments consisted of an essay test of critical-thinking skills and an instructional implementation observation sheet. The data were analyzed using tests of normality and homogeneity followed by one-way ANOVA. The results indicated that Wordwall-assisted discovery learning had a statistically significant effect on students’ critical-thinking skills, p < .001; therefore, H0 was rejected and Ha was accepted. The findings suggest that Wordwall-assisted discovery learning may be used as an alternative instructional approach to promote student engagement, conceptual understanding, and critical-thinking skills in the topic of the human reproductive system.